Pengembangan Kue Bawang Rendah Gluten dengan Substitusi Tepung MOCAF (Modified Cassava Flour) - Mesa Saputri; Desy Kurniawati (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
Food is a basic need that must be met by every individual. In Indonesia, rice is still the main staple food, but the shift in consumption to rice and wheat which are imported foodstuffs raises concerns about food security. Therefore, the development of local food alternatives such as MOCAF (Modified Cassava Flour) flour from cassava is important. In this practicum, MOCAF flour was made through a cassava fermentation process, followed by making onion cakes using the MOCAF flour. Organoleptic tests and XRF tests were carried out to evaluate the quality of MOCAF flour. The results of the practicum showed that the substitution of MOCAF flour in making onion cakes can produce low-gluten products that have the potential to be a sustainable food alternative.